Perfil Clínico-epidemiológico dos casos com suspeição diagnóstica de tromboembolismo pulmonar no hospital universitário João de Barros Barreto (HUJBB) no período de 2015 a 2021 - BECHARA, Luis Felipe de Oliveira (2023)
Pulmonary thromboembolism (PTE) results from the detachment of a thrombus originating in the deep venous system or right heart cavity, and subsequent occlusion of the pulmonary artery or its branches. It has a non-specific clinic and diagnosis with chest angiotomography. When untreated, it has about 30% lethality. The objective of this work is to analyze PTE in hospitalized patients. For this purpose, a retrospective cohort study of the clinical-epidemiological profile of patients with suspected pulmonary thromboembolism was carried out at the University Hospital João de Barros Barreto, between 2015 and 2021, with analysis of 48 medical records. In the study, 50% are female, although males are more exposed to risk factors for PTE. Most cases (47.9%) are between 60 and 98 years old, with the sixth decade of life being the most affected age group, in cases diagnosed as PTE. In accordance with the representativeness of the region, 91.7% of the color/race declared to be brown. The hospitalization time of up to 30 days in 66.7% of cases is above the average of 8.7 days for the year 2019. There was a recurrence of 10.4% in 6 months for hospitalization, which is possible in up to a third of the cases. Immobility, with 45.8%, was the most expressive risk factor, and increases the probability of PTE by two to five times. The clinic related to the existence of cancer, with 33.3% of the cases, had a higher prevalence, and in the presence of chemotherapy, an increase in the risk of a thrombotic event by two to six times. There was no diagnosis of PTE, and the tests performed are for existing comorbidities. The Wells score showed probable PTE in 57.1% of 7 diagnoses of deep vein thrombosis (DVT) performed. Death is higher in males (56.3%), which has a higher mortality in PTE. The risk factors and comorbidities, metastasis (p=0.039) and DVT (p<0.001) had statistical significance, where 25% of deaths had metastasis and 100% of deaths without DVT, despite being together with PTE, the main preventable causes of death in hospitalized patients. It is concluded that the clinical-epidemiological data did not disagree with the literature. The existence of DVT increases the probability of PTE, and metastasis is a risk factor, in addition to comorbidity, associated with death. Research is needed to make a diagnostic protocol in the absence of the ideal diagnostic method.